Environmentalism for Nature to Environmentalism for Profit - Widyana, Maulida Rita; Salsabila, Ayna Jamila; Yeuyanan, Herry Pragus (PCD Press, Department of Politics and Government - Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2023)
This research discusses the discourse related to the mining of andesite stone for the construction of the Bener Dam in Purworejo, Central Java, as part of the National Strategic Project. The discourse constructed among actors is highly diverse. The dominant discourse is led by the government, which views the use of the forest for environmentalism for profit, while local residents see the forest as environmentalism for nature. Michel Foucault's discourse theory on the production of knowledge and power underscores the discourses brought forth by the government, the community, and NGOs. Meanwhile, Anja Nygren's concept of environmental discourse complements the various discourses that have emerged. The objective of this research is to observe the dynamics and discourse constructed by pro and contra actors regarding the construction of the Bener Dam. The research utilizes both primary and secondary data, with primary data obtained through direct interviews with sources such as Indonesian Forum for the Environment of Yogyakarta, Community Movement for Environmental Care in Wadas Village (GEMPADEWA), and Legal Aid Institute of Yogyakarta. The conclusion drawn from this research is that the dominant discourse constructed by the government can influence public opinion, especially through negotiations that lead to mutually beneficial agreements.